Hakikat Cinta dalam Kehidupan Manusia Perspektif Armada Riyanto - Mathias Jebaru Adon (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This study is motivated by the realization that love is a rich dimension of human life. Every stage of the human life journey is influenced by the power of love, making the meaning of love a field of deep philosophical exploration. The purpose of this research is to interpret the nature of love in human life from the perspective of Armada Riyanto’s philosophy. According to Armada Riyanto, love is something that all humans long for, that they hope for, strive for, and experience in life. This research uses qualitative methods and finds that each stage of the experience of love provides an enchanting experience and shows the infinite richness of life. The result of this study contributes to the understanding of love as a unique and profound experience in human life.